Diagnostik und chirurgische Therapie der Schilddrüsenerkrankungen: Referate - Verse, Thomas; Chromik, Ansgar Michael (HNO, 2025)
There is a growing interest in diseases of the thyroid gland within the ENT community. This review provides an introduction to the topic. The first section describes the surgical anatomy and physiology of the thyroid gland. Subsequently, the most frequent benign and malignant diseases of the thyroid gland are discussed. Regarding treatment of thyroid diseases, the focus is placed on surgical therapy with all its perioperative issues as well as surgical complications and their management.